Structure and Classification of Legal Norms: Institutional Challenges in Law Making - Nazhif Ali Murtadho; Reni Andreyani; Ryszhard Ken Sakti; Nizar Rahmatullah; Yusya Rugaya Salsabilah; Suleman Watae (Universitas Negeri Surabaya, 2024)
This research analyzes how the institutional testing of legal norms in Indonesia, specifically discussing the institutional problems. This research is a normative legal study with the approaches used being the statutory approach and the conceptual approach. The study results indicate that several issues, including the arrangement, structuring, classification of norms, and how to regulate the hierarchy of legal norms, have been identified. Legal norms are fundamentally very close to the values believed by society, but the strength of the law's enforceability has not yet been able to detach itself from the institutional power, so law, society, and power are elements of a social order. Therefore, law should not only be understood as a norm that guarantees satisfaction and justice but also must be viewed from the perspective of justice and utility. The conclusion of this research is that legal norms essentially begin with planning, preparation, drafting techniques, formulation, discussion, approval, promulgation, and dissemination.